Liquid Asset Ratios and Financial Sector Reform - Gulde, Anne. (Washington, D.C. : International Monetary Fund, 1997)
As a monetary, selective credit, and government debt-management instrument, a liquid asset ratio is generally inefficient and may introduce serious distortions. However, it may play a limited role as a prudential instrument, particularly in less sophisticated banking systems or in the context of currency board arrangements. Recent trends in the use of this instrument have been to either abolish it altogether or to design it so as to minimize distortions. When necessary, these changes have been part of a broader effort to make financial intermediation more efficient by relying more on markets and less on regulations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet